THE CORRELATION BETWEEN FAMILY SUPERVISION OF SCREEN TIME WITH THE INCIDENCE OF GADGET ADDICTION IN JUNIOR HIGH SCHOOL CHILDREN - Salsabila, Athaya; Mundijo, Trisnawati; Kesuma, Putri zalika lailah mardiah; Awang, Zarinah Binti (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Rapid technological developments have increased the use of gadgets among children and teenagers. Devices provide benefits in the form of easy access to information, but excessive use can have negative impacts, including adding gadgets. Children aged 12-15 years are the group most vulnerable to the negative impacts of gadgets. Families, especially parents, play an important role in supervising and guiding children in using devices. This research aims to determine the relationship between family supervision of screen time and the incidence of device addiction in junior high school children. This type of research is quantitative with a cross sectional design using primary data from the community of Kelurahan 5 Ulu Palembang with 91 samples that have met the inclusion and exclusion criteria. This research sample was taken by means of consecutive sampling. The results of the statistical test obtained a P-value of 0.000, so it can be concluded that there is a correlation between family supervision of screen time and the incidence of gadget addiction in junior high school children.